Математичні моделі цінової конкуренції залізничної та промислових монополій - Петренко, О.Д.; Петренко, О.О. (Економіка промисловості, 2013)
Запропоновано лінійну математичну модель «цінової гонки», яка описує міжгалузеву конкуренцію монополій. Встановлено, що цінові диспропорції між ними можуть бути усунені лише за умови зовнішнього регулювання з боку держави. Предложена линейная математическая модель «ценовой гонки», которая описывает межотраслевую конкуренцию монополий. Установлено, что ценовые диспропорции между ними могут быть устранены только при условии внешнего регулирования со стороны государства. As evidenced by the world practice, the balance in economic systems never strikes, and it requires studying them as a part of a dynamic approach in the image and likeness of natural sciences involving mathematical modeling. Price is the main instrument of market relations. In developed markets there is a free pricing achieved by free bargaining between the seller and the buyer. In the transition economies of Ukraine in new economic conditions it was assumed that the price liberalization establish the optimal proportions (by the "invisible hand"). In fact, at the initial stage of reforms everything went exactly the opposite way - the prices were exploded and did not reach equilibrium, and such a disparity initiated a continuous inflationary spiral. One of the main objectives of reforming the Ukrainian railways is to reduce costs and, consequently, the cost of transportation. However, contrary to the logic of the reforms, the question is not constantly on the reduction under the assumption of a tariff increase. The rates for rail transport grow not only due to the desire to increase its monopoly profits, but also to the inflationary pressure in economy, and as the main argument of their increase is the rise in prices for basic products consumed by the industry. In this case, however, it is left out of the question to what extent the very "UZ" may affect inflation. Responding to their direct function, i.e. transportation, railways of Ukraine should maintain the structural balance of the national economy. The prices (tariffs) for their services have the most profound effect on the economy. Railway transportation tariff is the price of carriage of goods or passengers established on the basis of the current cost of transportation, supply and demand taking into account the price for other transport modes, as well as in other ways.